(untitled) (Altre Modernità, 2014)
In his essay Wilson also inaugurates the fortunate metaphor of East and West (epitomised by the lama Teshoo and Colonel Creighton) as parallel worlds that never meet, less than ever at the end of the novel. Subsequent criticism, including Said’s highly influential introduction to the Penguin edition of Kim